Fabricação artesanal e avaliação química e microbiológica do queijo colonial produzido em municípios do oeste do território da Cantuquiriguaçu Paraná/Brasil - Tesser, Ionara Casali (2014)
Three municipalities from the west of the Cantuquiriguaçu region (Paraná state) were chosen to this study, which examined the production and centesimal composition of the colonial cheese produced in the region. The research also aimed provide to the actors involved in the process knowledge concerning the production and improvements of the cheese in order to guarantee the quality of the product and support the rural worker that performs this activity. 17 rural properties were visited and were applied a survey questionnaire in order to understand the milk production and the production conditions of the cheese. Following the Normative Instruction nº 30/2013 from MAPA (Brazilian Ministry of Agriculture, Livestock and Food Supply), microbiological and compositional analyses were made on the cheese from the visited properties aiming to typify the artisanal colonial cheese produced on those municipalities. The results will become important supports to the adoption of municipal public policies intending not only the continuity of the production, and its improvement, but also the consumers safety